Fostering place-based innovation and internationalization – the new turn in German technology policy - Dirk Dohse; Dirk Fornahl; Julian Vehrke (European Planning Studies, 2018)
Since the mid-1990s German technology policy has experienced a paradigmatic shift from standard grant schemes towards a region-oriented and competition-based R&D policy. Currently, a new policy experiment, the InterClust contest, is under way, trying to simultaneously foster place-based innovation, R&D internationalization and the internationalization of innovative places. The current paper analyses the new policy, relating it to the recent literatures on heterogeneous firms and on cluster-life cycles, and presents results from a firm survey performed in 21 winner regions of InterClust. Findings show that the new funding scheme takes insights from recent theoretical developments into account and addresses important impediments to firm and cluster internationalization. Although it is too early for an overall assessment, it is argued that the long-term impact will critically depend on the inflow of heterogeneous knowledge and the strength of intra-regional mobilization effects.
Keywords: O30; R11; F61; 330; industrial clusters; knowledge spillovers; technology policy